Harmonia entre a OBMEP e a resolução de problemas nos anos finais do ensino fundamental - Pereira, Brenda Vaz (Universidade Federal de São Carlos, 2022)
This paper reports a professional experience with students from the final years of elementary school who were part of a study group in which questions from previous OBMEP tests were used for the teaching and learning of mathematics, through the use of the problem-solving methodology proposed by POLYA (2006) and ONUCHIC (2012), with remote encounters, due to the pandemic period of COVID-19 and face-to-face. After the return of classes in the school units, a joint work was developed between teachers and students from 6th grade to 9th grade in order to rescue the teaching of mathematics and prepare students for the realization of OBMEP 2021. It had an analytical and methodical view at the development of activities from the elaboration of lists in which the selected questions were allusive to the skills of BNCC and the Paulista Curriculum, according to the school time in which the students were enrolled. This work presents the improvement in the personal and social performances of students in the school and family environments, considering that the family was a fundamental agent in the development and constancy of the project and the evolution in the group's personal and collective studies and achievements.
Harmony between OBMEP and problem-solving in the final years of elementary school
Keywords: Ensino de matemática; OBMEP; Resolução de problemas; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO